Natal host plants can alter herbivore competition - Pan, Huipeng; Preisser, Evan; Su, Qi; Jiao, Xiaoguo; Xie, Wen; Wang, Shaoli; Wu, Qingjun; Zhang, Youjun (PeerJ PrePrints, 2014)
Interspecific competition between herbivores is widely recognized as an important determinant of community structure. Although researchers have identified a number of factors capable of altering competitive interactions, few studies have addressed the influence of neighboring plant species. If adaptation to/ epigenetic effects of an herbivore’s natal host plant alter its performance on other host plants, then interspecific herbivore interactions may play out differently in heterogeneous and homogenous plant communities. We tested the impact of natal host plants on interactions between the Middle-east Asia Minor 1 (MEAM1) and Mediterranean (MED) cryptic species of the whitefly Bemisia tabaci by rearing the offspring of a cabbage-derived MEAM1 population and a poinsettia-derived MED population together on three different host plants: cotton, poinsettia, and cabbage. We found that MED excluded MEAM1 on poinsettia and that MEAM1 excluded MED on cabbage, results consistent with previous research. MED also excluded MEAM1 when reared together on cotton, however, a result at odds with multiple otherwise-similar studies that reared both species on the same natal plant. Our work provides evidence that natal plants affect competitive interactions on another plant species, and highlights the potential importance of neighboring plant species on herbivore community composition.
Keywords: Adaptation; transgenerational impacts; maternal effects; host plant effects; competitive displacement; Bemisia tabaci